Electrocoagulation for ammonium removal in Nam Son landfill leachate - Son, Le Thanh; Khai, Le Cao; Ha, Nguyen Thi; Linh, Doan Tuan; Anh, Doan Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 33 No 2DO - 10.25073/2588-1094/vnuees.4047, 2017)
In this paper, an electrocoagulation reactor was set up to investigate the ammonium removal in Nam Son landfill leachate. The research focused on studying several factors that affect to the ammonium removal namely current intensity, operating time, initial pH and electrode materials. A mono-polar electrocoagulation reactor was set up in a batch system with iron electrodes and 1.8 L leachate. The research indicated that current intensity and operating time are directly proportional with NH 4+ treatment performance. When applied current increased from 1 to 4A, the NH 4+ removal percentage went up from 14.03 to 24.99% after a 1 hour treatment. The effect of initial pH in range of 5 to 10 has showed that the best NH 4+ treatment efficiency in neutral and mild alkaline conditions. It is noticeable that iron electrodes had higher NH 4+ removal than aluminum one during nearly the first 40 min, however this trend has been reversed later with the advantage belonging to aluminum anode. The optimum operating conditions found are aluminum electrodes, applied current of 3A, electrolysis time of 60 min, raw pH of 8, resulting in NH 4+ treatment performance of approximately 24%. As a result, the electrocoagulation method is not really effective in NH 4+ removal and might be applied as a pre-treatment. Keywords Ammonium, electrocoagulation, landfill leachate, iron, aluminum, electrodes References [1] I. Linares-Hernández, C. Barrera-Díaz, G. Roa-Morales, B. Bilyeu, F. Ureña-Núñez, Influence of the anodic material on electrocoagulation performance, Chemistry of Engineer Journal, 148, 2009, 97-105. [2] C.B. Shivayogimath, W. Chandrakant, Landfill leachate treatment by electrocoagulation process using iron sacrificial electrodes, International Journal of Renewable Energy and Environmental Engineering, 02, 2014, 3. [3] M. Mollah, P. Morkovsky, J.A.G. Gomes, M. Kesmez, J. Parga, D.L. Cocke, Fundamentals, present and future perspectives of electrocoagulation, Journal of Hazardous Materials, B 114, 2004, 199–210. [4] N. Daneshvar, A. Oladegaragoze, N. Djafarzadeh, De-colorization of basic dye solutions by electrocoagulation: an investigation of the effect of operational parameters, Journal of Hazardous Materials B,129, 2006, 116–122. [5] M. Kobya, O.T. Can, M. Bayramoglu, Treatment of textile wastewaters by electrocoagulation using iron and aluminum electrodes, Journal of Hazardous Materials B, 100, 2003, 163–178. [6] Nguyen Manh Khai, Hoang Thi Quynh Trang, Chemical Precipitation of Ammonia and Phosphate from Nam Son Landfill Leachate, Hanoi, Iranica Journal of Energy and Environment, 3, 2012, 32-36. [7] Hoang Viet Yen, Doctor Thesis of Science: Optimization of partial nitrification and de-nitrification processes in landfill leachate treatment using sequencing batch reactor technique, Université de Liège, 2009. [8] Phan The Nhat, Ha Nhu Biec, Nguyen Thi Tuyet Mai, Bui Xuan Thanh, Nguyen Phuoc Dan, Application of a partial Nitritation and anammox system for the old landfill leachate treatment, International Bio-deterioration and Biodegradation 95, 2014, 144-150. [9] I. Fatih, K. Ugur, A. Omer, M. Talha Gonullu, Treatment of leachate by electrocoagulation using aluminum and iron electrodes, Journal of Hazardous Materials, 154, 2008, 381-389. [10] X. Chen, G. Chen, P.L. Yue. Separation of pollutants from restaurant wastewater by electrocoagulation, Separation Purification and Technology, 19, 2000, 65-76. [11] X. Li, J. Song, J. Guo, Z. Wang, Q. Feng, Landfill leachate treatment using electrocoagulation, Procedia Environmental Sciences, 10, 2011, 1159-1164. [12] E. Bazrafshan, Performance evaluation of electrocoagulation process for removal of chromium (VI) from synthetic chromium solutions using iron and aluminum electrodes, Turkish Journal of Engineering and Environmental Science, 32, 2008, 59–66. [13] X. M. Chen, G.H. Chen, P.L. Yue, Separation of pollutants from restaurant wastewater by electrocoagulation, Separation and Purification Technology,19, 2000, 65–76. [14] M. Kobya, H. Hiz, E. Senturk, C. Aydiner, E. Demirbas, Treatment of potato chips manufacturing wastewater by electrocoagulation, Desalination, 190, 2006, 201–211.